Manufacturing backshoring in Europe - myth or reality? - Palčič, Iztok; Ojsteršek, Robert (Anali PAZU HD, 2022)
Backshoring – the movement of manufacturing activities from locations abroad to the home country – has gained prominence in public policy discussions and in academic research in recent years. Despite this prominence, empirical evidence on backshoring still exists mostly in the form of case studies. This paper presents empirical evidence on backshoring from a large sample of European manufacturing firms. The data indicate that backshoring is still uncommon among European firms. Around 4% of all firms in our sample have moved production back to the home country between 2013 and mid-2015. The most frequent reasons for backshoring are the loss of flexibility, a lack in quality of the goods produced abroad, and unemployed capacities at home. Flexibility and quality concerns are, in particular, relevant for firms that move production back from Asian countries. Backshoring is most likely for manufacturers of final products and in high-technology sectors, in particular in electrical equipment, information and communications equipment, and the automotive industry.
Keywords: backshoring; offshoring; motives; manufacturing company; European Manufacturing Survey